Metformin for endometrial hyperplasia: a Cochrane protocol. Issue 8 (16th August 2016) - Clement, Naomi S; Oliver, Thomas R W; Shiwani, Hunain; Saner, Juliane R F; Mulvaney, Caroline A; Atiomo, William
Abstract : Introduction: Endometrial hyperplasia is a precancerous lesion of the endometrium, commonly presenting with uterine bleeding. If managed expectantly, it frequently progresses to endometrial carcinoma, rates of which are increasing dramatically worldwide. However, the established treatment for endometrial hyperplasia (progestogens) involves multiple side effects and leaves the risk of recurrence. Metformin is the most commonly used oral hypoglycaemic agent in type 2 diabetes mellitus. It has also been linked to the reversal of endometrial hyperplasia and may therefore contribute to decreasing the prevalence of endometrial carcinoma without the fertility and side effect consequences of current therapies. However, the efficacy and safety of metformin being used for this therapeutic target is unclear and, therefore, this systematic review will aim to determine this. Methods and analysis: We will search the following trials and databases with no language restrictions: Cochrane Gynaecology and Fertility Specialised Register; Cochrane Central Register of Controlled Trials (CENTRAL); MEDLINE; EMBASE; EBSCO Cumulative Index to Nursing and Allied Health Literature; PubMed; Google Scholar; ClinicalTrials.gov; the WHO International Trials Registry Platform portal; OpenGrey and the Latin American and Caribbean Health Sciences Literature (LILACS). We will include randomised controlled trials (RCTs) of use of metformin compared with a placebo or no treatment, conventional medical treatment (eg, progestogens) or any other active intervention. Two review authors will independently assess the trial eligibility, risk of bias and extract appropriate data points. Trial authors will be contacted for additional data. The primary review outcome is the regression of endometrial hyperplasia histology towards normal histology. Secondary outcomes include hysterectomy rate; abnormal uterine bleeding; quality of life scores and adverse reactions to treatments. Ethics and dissemination: Dissemination of the completed review will be through the Cochrane Library as well as through presenting the results at appropriate conferences.